Latobici publice patrono… Die Ehreninschrift für einen Patronus von Neviodunum (ILSl 1, 25 = CIL III, 10804) - Špendal, Žan; Lovenjak, Milan (Arheološki vestnik, 2025)
The article discusses a partially preserved honourific inscription to the patron of Neviodunum (municipium Flavium Latobicorum Neviodunum), which was discovered in the 19th century at the Mokrice castle (Slovenia). Neviodunum received the rights of an autonomous town during the period of the Flavian emperors, so Vespasian’s appearance is considered the terminus post quem for the selection and honouring of a senator. His name is not preserved in the fragment, but only three stages of his career. Based on these, the honouree cannot be reliably linked to any known person. According to one interpretation, the inscription could refer to the course of the early career of the Roman senator and historian Cornelius Tacitus before he assumed the function of suffect consul in 97.